c-Jun N-Terminal Kinase (JNK) Inhibitor IQ-1S as a Suppressor of Tumor Spheroid Growth; Molecules; Vol. 30, iss. 21 - Afrimzon E. Elena; Deutsch M. Mordechai; Sobolev M.; Naomi Zurgil; Khlebnikov A. I. Andrey Ivanovich; Buldakov M. A. Mikhail Aleksandrovich; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich (2025, 2025)
Title screen